2014
DOI: 10.1007/s40620-013-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

The nephrologist’s anticoagulation treatment patterns/regimens in chronic hemodialysis patients with atrial fibrillation

Abstract: A high AF prevalence was observed in our HD population, but less than 50 % of these patients received OAT. Patients with permanent AF were more frequently treated with warfarin, while OAT administration was uncommon in those with previous bleedings. The thromboembolic risk score was not associated with warfarin prescription, while there was an inverse relation with the hemorrhagic risk score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…We found that several predictors of stroke risk including advanced age, history of diabetes and myocardial infarction were inversely associated with warfarin initiation, which differed from Genovesi et al's observation that these factors were not significantly associated with warfarin prescription [37]. The magnitude of these factors reported by Genovesi et al were in the same direction as ours (i.e.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…We found that several predictors of stroke risk including advanced age, history of diabetes and myocardial infarction were inversely associated with warfarin initiation, which differed from Genovesi et al's observation that these factors were not significantly associated with warfarin prescription [37]. The magnitude of these factors reported by Genovesi et al were in the same direction as ours (i.e.…”
Section: Discussioncontrasting
confidence: 95%
“…We found that bleeding history was inversely associated with warfarin initiation, but bleeding risk score and stroke risk score were not associated after adjustment for other patient characteristics. Genovesi et al found that previous bleedings and hemorrhagic risk score was inversely related to warfarin use, but stroke risk score was not associated with warfarin use [37]. Such discrepancy might be due to differences in the study population and the definition of warfarin use: Genovesi et al studied a mixed population of new and chronic warfarin among chronic HD patients with AF in Italy [37], whereas we studied new users among older adults undergoing HD or PD with incident AF in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Continued warfarin therapy in a form of "prescriptive inertia" was followed by the influence of the dominant practice guideline [17]. Gevovesi study reported that 44.5% of HD patients and AF received oral anticoagulation (OAT) [18].…”
Section: Introductionmentioning
confidence: 99%
“…The CHADS 2 score is not associated with warfarin prescription. This turns into a low prevalence of warfarin prescription (less than 50% of the patients) [27]. In this specific setting characterized by a very high mortality, anticoagulation seems to be associated with a better survival; furthermore, patients with the highest time of International Normalized Ratio (INR) in therapeutic range had the lowest bleeding rate [28].…”
Section: Estimation Of Renal Functionmentioning
confidence: 99%